Digital health in a social health insurance system: new emergent market powers in Germany. (30th September 2020) - Posselt, J; Kuhlmann, E
Abstract: Background: This presentation analyses the dynamics of digital health from a governance perspective. It aims to explore the driving forces for the implementation of digital health in Germany. Germany is chosen as a case study of a social health insurance system, which is based on joint self-governance of sickness funds and providers, and strong corporatist power of the medical profession. Methods: A qualitative explorative approach is applied, drawing on document analysis and other secondary sources. The research is based on a governance approach adapted from Glassman and Buse's model of public health policy reform. Results: The WHO Global Strategy for Digital Health 2020-2024 serves as a key international policy framework. However, the analysis reveals firstly that implementation is shaped by national healthcare systems and may create different results; secondly, the global strategy provides only a weak guidance on the national level. In Germany, strong corporatism and weak state intervention is supporting market forces and private actors. Poorly developed digital health governance has opened a window of opportunity for market powers as driving forces for digital health, thus creating new risks of social inequalities. There is an urgent need for public health to step up advocacy for health literacy to improve the accessibility to digital health for all citizens. Conclusions: National healthcare systems strongly shape the implementation of international digital health frameworks, which makes digital health an issue of governance. Stronger public health orientation and a people-centred approach are needed to counteract new emergent social inequalities created by market power. Key messages: Market power and private actors are important drivers of digital health in the German healthcare system. Social health insurance systems may be vulnerable to market powers and new digital health inequalities.